Influence of Digital Marketing, Brand Image, and Service Quality on Nasabah Decision to Use Indonesia Syariah Bank Services (Case Study of Generation Z in Tegal City) - Alawiyah, Nafisatul; Mohammad Rosyada (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2025)
Digital transformation in the Industrial Revolution 4.0 era has driven the banking sector, including BSI, to offer technology-based services such as the BYOND by BSI application. Generation Z is the main target due to their high digital engagement. However, their interest and understanding of Islamic banking remain varied, especially in Tegal City, where participation is still low despite a Muslim majority. This study analyzes the influence of digital marketing, brand image, and service quality on Generation Z’s decision to use BSI services in Tegal City. This research employed a quantitative approach with a survey method and associative causal type. The population comprised Generation Z aged 18–28 years, with a sample of 96 respondents selected through purposive sampling. Data were collected using a questionnaire with Likert scale and analyzed through validity, reliability, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS. The results indicate that digital marketing and service quality have a positive and significant effect on Generation Z’s decision to use BSI services, while brand image does not have a significant partial effect. However, simultaneously, the three variables have a positive and significant influence. These findings suggest that strengthening digital marketing strategies and improving service quality are dominant factors in influencing young customers’ decisions.